THE INFLUENCE OF STAKEHOLDERS IN EVALUATING THE IMPLEMENTATION OF GREEN ENTREPRENEURSHIP BY UNIVERSITY GRADUATES - Rachmawati, Dita; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (International Journal of Business, Law, and Education, 2023)
This research aims to give input to decision-makers so that stakeholders can create appropriate regulations to help evaluate the application of green entrepreneurship, in the sense of being able to improve community welfare and environmental sustainability by involving stakeholders and collaborating which is the result of the Merdeka Belajar Kampus Merdeka learning scheme. The analysis uses a descriptive approach to analyze respondents' information regarding gender, domicile, business ownership, type of business start-up, involvement in social activities, and type of social activity as a reflection of the green behavior that has been carried out by the respondent. The analysis technique uses multiple structural regression with IBM SPSS-26 software. The results of the study show that the formation of a green economy which is monitored and evaluated by stakeholders is expected to support the growth of student interest in green entrepreneurship in the future